Transcriptional regulation of the glucoamylase-encoding gene under endoplasmic reticulum stress in Aspergillus niger - Al-Sheikh, Hashem M. (2005)
The ability of many filamentous fungi, such as Aspergillus niger, to secret a high level of homologous proteins has led to their consideration as hosts for the production of heterologous proteins. However, the levels of some secreted heterologous proteins have often been low. Although many strategies have been developed to improve the level of secreted heterologous proteins, further studies into the remaining bottlenecks are required. One common strategy used to improve secreted protein production from filamentous fungi is to express the target protein under the control of a highly-induced native promoter. One major bottleneck in the secretion of heterologous proteins is caused by the folding of proteins within the lumen of the endoplasmic reticulum (ER). Recent studies have shown that expressing some heterologous proteins could subject A. niger to ER-stress. In this study, A. niger was subjected to different environmental conditions and ER stress responses were examined under each of these environmental conditions to further investigate the regulation of the gene encoding glucoamylase (glaA). Treating A. niger with dithiothreitol (OTT), a reducing agent that causes the formation of unfolded proteins, caused the down-regulation of transcription of the glaA but not the gene encoding the non-secreted protein y-actin. The OTT-treated fungal cells also showed evidence of induction of the UPR because expression of bipA was up-regulated and splicing of hacA, the gene encoding the transcription factor responsible for induction of the Unfolded Protein Response (UPR), occurs allowing the production of an active HacA protein. This is the first study to show clearly by nuclear run-on studies that the transcriptional down-regulation effect occurs at the level of transcription, rather than mRNA stability, and is found to be mediated through the promoter of the glaA gene (PglaA) in a region more than 1.192 kb upstream of the translational start.